Microsurgical Treatment of Posterior Cerebral Artery Aneurysm (P2P Segment): Case Report and Review of the Literature - Meguins, Lucas Crociati; Spotti, Antônio Ronaldo; de Oliveira, Jean Gonçalves; Pereira, Carlos Umberto; Fernandes, Ronaldo Brasileiro de Miranda Batista; Santos, Herbert Cunha Moreira; Valsechi, Linoel Curado; Rodrigues, Thayanna Bentes Lemanski Lopes; de Morais, Dionei Freitas (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Introduction Aneurysms of the posterior cerebral artery (PCA) represent ∼ 1% of all intracranial aneurysms and usually present with subarachnoid hemorrhage.Objective The aim of the present study is to describe the case of an adult man presenting a saccular aneurysm of the right PCA at the posterior half of the postcommunicating (P2P) segment, and to discuss the technical nuances of the approach and of the clipping process.Case Report An investigation of a chronic headache in a 55-year-old man found a saccular aneurysm located just posterior to the most lateral portion of the right cerebral peduncle. A digital subtraction arteriography revealed a 7.8 mm × 5.6 mm × 4.8 mm posterior-medial projecting aneurysm of the right PCA at the P2P segment. A subtemporal approach was performed with partial aspiration of the right parahippocampal gyrus for a better exposure of the vascular structures. A proximal temporary occlusion of the PCA was performed at the anterior half of the postcommunicating P2A segment. The aneurysm was clipped with two semi-curved clips. The patient presented an uneventful recovery and was discharged from the hospital on the third postoperative day without any additional neurological deficits.Conclusion Aneurysms of the PCA are an uncommon vascular disease that challenges the ability of the neurosurgeons due to their many anatomical nuances, to their vast number of perforators, and to the risk of bleeding. However, the operative management of aneurysms of the PCA is technically feasible, safe and effective when performed respecting microsurgical principles.
Keywords: posterior cerebral artery (PCA); aneurysm